2011
DOI: 10.3184/095422911x13028018264633
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and bioaccumulation of copper and zinc in wetland soils of the Niger Delta determined by the oil palm

Abstract: The concentration, mobility, bioavailability, distribution and associations of two essential micronutrient elements (copper and zinc) to the oil palm in wetland soils of the Niger delta region of Nigeria was assessed by means of chemical fractionation analysis. The water soluble and plant available fractions were introduced into the sequential extraction scheme. Also assessed were the bioaccumulation (concentration and distribution) of these metals in the leaves and fruits of the oil palm of various ages found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
5
4
0
Order By: Relevance
“…The highest mean value of 6.389 mgkg-1 equivalent to 46.63% of the total copper concentration was observed in the soils derived from alluvium while the lowest mean value of 2.231 mg kg -1 equivalent to 45.42% of the total Copper concentration was recorded in the soils derived from the Imo clay shale. A comparison with the other copper fractions showed that the Fe-Mn bound copper was the most dominant fraction which is consistent with the reports of Kabat-Pendias and Pendias (2001) and that of Oviasogie et al (2011) for alluvial soils of the Niger Delta, Nigeria. Kabata-Pendias (2011) had reported that the greatest amounts of adsorbed Cu have always been found in Fe and Mn oxides (hematite, goethite, birnessite), amorphous Fe and Al hydroxides, and clays (Kabata-Pendias, 2011) which could be due to adsorption mechanism of copper onto metal oxides.…”
Section: Fractions and Distribution Of Copper In The Soilssupporting
confidence: 90%
See 4 more Smart Citations
“…The highest mean value of 6.389 mgkg-1 equivalent to 46.63% of the total copper concentration was observed in the soils derived from alluvium while the lowest mean value of 2.231 mg kg -1 equivalent to 45.42% of the total Copper concentration was recorded in the soils derived from the Imo clay shale. A comparison with the other copper fractions showed that the Fe-Mn bound copper was the most dominant fraction which is consistent with the reports of Kabat-Pendias and Pendias (2001) and that of Oviasogie et al (2011) for alluvial soils of the Niger Delta, Nigeria. Kabata-Pendias (2011) had reported that the greatest amounts of adsorbed Cu have always been found in Fe and Mn oxides (hematite, goethite, birnessite), amorphous Fe and Al hydroxides, and clays (Kabata-Pendias, 2011) which could be due to adsorption mechanism of copper onto metal oxides.…”
Section: Fractions and Distribution Of Copper In The Soilssupporting
confidence: 90%
“…The specifically sorbed/carbonate Cu content of the soils based on their parent materials was in a decreasing order of alluvium > coastal plain sands > Imo clay shale > false bedded sandstones. The values obtained for the soils of the alluvium and falsebedded sandstones were similar to those the reported by Oviasogie et al (2011) in the wetland (Alluvium) soils of the Niger Delta, Nigeria and those reported by Yu et al (2004) for some Inceptisols derived from sandstones in China, respectively. The results further showed decreasing concentration of the specifically sorbed/carbonate with depth in the soil derived from the alluvium but the distribution in the other soils did not follow any well-defined pattern.…”
Section: Fractions and Distribution Of Copper In The Soilssupporting
confidence: 87%
See 3 more Smart Citations